Bill 2 : Smile No. - Peeters, Julie; Narbutaité, Elena (Amsterdam : Roma Publications, 2019)
Peters, Bart Julius ; Woo, Ann ; Lempert, Jochen ; Sullivan, Megan Francis : Schmid, Reto ; Kurahashi, Tadashi ; Yokoo, Tadanori ; Zhang, Jiajia ; Dodge, Jason ; van Deursen, Linda ; Didziapetris, Gintaras ; Ketelers, Inge ; Hollein, Hans ; RareBooksParis
boek